Pengujian sifat unggul beberapa klon harapan kopi arabika di kebun percobaan Andungsari, Jawa Timur (Testing for superior traits of some arabica coffee promising clones at Andungsari research station, East Java) - Retno Hulupi; Surip Mawardi; Yusianto Yusianto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2012)
One of the major diseases which limiting production in arabica coffee is the leaf rust caused by the fungus Hemileia vastatrix, B et Br. Selection and testing on thirteen promising arabica coffee clones were carried out at endemic area for leaf rust disease, Andungsari Research Station, for six fruiting times. The aims of these test were to find out superior planting material as clone with genetic resistance to leaf rust. As the beverage commodities, criterium selections for superiority clone besides resistant to leaf rust and yielding ability of more than 1,5 ton/ha also must be excellent in cup quality. Under this consideration, BP 416 A clone showed as the best high yielding ability i.e. 1,595 kg/ha and stable, besides resistant to leaf rust disease compared to the other clones tested. This clone had good cup quality, better than earlier released variety such as USDA 762 and S 795 although was not better than Andungsari 1 that were planted in the same location. The best physical bean characteristics was obtained on BP 513 A clone wich is derived from S 795 x Caturra red, having 89.2% of normal bean and 18.3% outurn characteristics. However, due to lower yielding and more susceptible to leaf rust, this clone could not be classified as superior clone.